Studi Sistem Dispersi Padat Gliklazid Menggunakan Polivinil Pirolidon K-30 (PVP K-30) dan Tween 80 - Halim, Auzal; Shilvi, Aulia; Erizal, Erizal (Jurnal Sains dan Teknologi Farmasi, 2011)
Solid dispersions of gliclazide were prepared by solvent evaporation method using PVP K-30 and Tween 80 as dispersion carriers. The  physicochemical characteristics of solid dispersions were evaluated using microscopic analysis, X-ray diffraction, differential thermal analysis, determination of recovery, and dissolution rate test. Difractogram X-rays showed the physical interaction between the drug (gliclazide) and carrier (PVP K-30 and Tween 80), and polymorphic transformation occured during the evaporation of solvent in the preparation of solid dispersion. Thermogram DTA showed that the components of PVP K-30 and Tween 80 used affected the position of endothermic peak and peak sharpness. Determination of gliclazide in the recovery of solid dispersion was done using derivative spectrophotometry. Solid dispersion of gliclazide-PVP K-30-Tween 80 prepared in this study were found to have higher dissolution rates than pure gliclazide.